Improvement of personnel management of internal affairs bodies on the basis of system analysis procedures - A. V. Rybak; R. M. Danilov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is to identify the main causes of the growing shortage of personnel resources of territorial divisions of internal affairs bodies (ATS) and appropriate methods of their elimination.Method. When searching for the causes of the personnel shortage of the ATS, the procedures of system analysis were used, on the basis of which the central problem of the staffing of the ATS was identified, a number of tasks and goals were formulated, for the solution of which additional material resources are not required. Mathematical methods of system dynamics were used to solve most problems.Result. In the work, based on the analysis of the operational situation, regulatory and methodological support of the management activities of the internal affairs bodies, it is concluded that there is a systemic problem: the dynamism of the management system of the internal affairs bodies is disrupted, as a result of which the effectiveness of the management process decreases, leading to an increasing trend of a shortage of ATS units. To solve the identified problems, the authors propose the following technologies: calculation of the profitability of the work of territorial divisions of the Ministry of Internal Affairs of Russia, which allows to assess the necessary and sufficient level of efficiency of the use of all types of resources in the performance of official tasks; development of a methodology for calculating the personnel needs of territorial divisions of the Ministry of Internal Affairs of Russia, taking into account the complexity of their activities, workload and regional characteristics; introduction of a new approach to assessing the activities of divisions The Ministry of Internal Affairs of Russia, based on the separation of the reporting system and the evaluation system, improving personnel policy in terms of making the service in the Department of Internal Affairs more attractive, taking into account the new values of modern society. For each presented task, its own tools and solution technology have been developed.Conclusion. The solution of the identified tasks will ensure the uniformity and "feasibility" of the workload of its employees, the transparency of the assessment of their activities, which will increase the motivation for conscientious work. Coupled with the improvement of personnel policy to make the service in the internal affairs bodies properly attractive, the expected synergetic effect will reduce the severity of the problem of personnel shortage.